Mental health first aid USA implementation: Trainee reported quality and impact of training. Issue 3 (25th November 2021) - Troxel, Mary; Anthony, Laura G.; Robertson, Hillary A.; Anthony, Bruno J.
Abstract: This study investigated the association of training implementation factors (Quality, Impact, Usefulness) with Mental Health First Aid (MHFA)‐targeted outcomes (e.g., increased knowledge, confidence helping someone). Trainees who completed MHFA USA training in 2016 ( N  = 1003) were surveyed post training about its influence on their thoughts and behaviors, and about implementation factors. Some trainees completed 3‐ and 6‐month follow‐ups ( N  = 430, N  = 276, respectively). Training Quality, Impact and Usefulness were rated highly. Differences in Quality and Impact across demographic groups were found; trainees from racially and ethnically marginalized backgrounds, and trainees with lower education levels, reported greater effect. Quality and Impact predicted positive changes in MHFA‐targeted constructs such as self‐efficacy, stigma and trainee perceived positive effect of MHFA strategies for those in crisis. Impact predicted positive change in mental health knowledge; this association strengthened over time. Results provide information about acceptability and perceived Impact of MHFA USA training and lead to recommendations for future evaluation and implementation.